Beyond Crystallinity: Using Raman Spectroscopic Methods to Further Define Aggregated/Supramolecular Structure of Cellulose - Agarwal, Umesh P. (Frontiers in Energy Research, 2022)
In the bio-based economy, conversion of biomass to biofuels and other products is essential for developing a sustainable alternative to fossil fuels. For this to become a reality, understanding of the biomass ultrastructure is critically important. For instance, to enhance the yield of fermentable sugars from enzymatic hydrolysis of cellulose, the understanding of the latter’s supramolecular structure and the ability to modify it appropriately is essential. Although cellulose crystallinity is one way to define the aggregated structure, previous research has shown that merely studying how cellulose crystallinity influences the hydrolysis is not good enough. This deduction is based on the fact that not only most crystallinity estimation methods have limitations but also crystallinity measurement inadequately defines the aggregated state of cellulose. Therefore, better approaches to describe the ultrastructure are needed. Raman spectroscopy is particularly well suited to this task because, in addition to crystallinity, several pieces of structure-related information can be generated, which when combined provide a more comprehensive description of the aggregated state. Additionally, the information derived using Raman spectroscopy is more resolved because it comes from spectral features that represent both the aggregated and the molecular states of cellulose. Few examples will be presented to illustrate this capability.